Implementation of Digital Literacy in the Development of Extracurricular Programs at Universitas Negeri Surabaya Laboratory Elementary School - M Fahmi Zakariyah; Yatim Riyanto; Gunarti Dwi Lestari; Ahmad Abdullah Zawawi (Edukasi, 2023)
This study aims to determine the implementation of digital literacy in the development of extracurricular programs in Unesa labschool elementary schools. This type of research is descriptive qualitative. Retrieval of data used using participatory observation and interview methods as primary data sources, then literature study used as secondary data. The results of the study show that Unesa Laboratory Elementary School applies digital literacy by incorporating an understanding of digital literacy in every extracurricular activity program starting from the process of planning, implementing, to evaluating. As for the implementation of digital literacy that has been implemented at Unesa Laboratory Elementary School, namely by using the ethics of collective awareness using social media for students to be included in every extracurricular activity so that students do not become addicted, victims of social media, and victims of negligence in time management. The control function carried out by the school is coordinating with parents of students and the surrounding community so that it becomes an important part of collaboration in using healthy technology for students at the elementary school level. This is better if it is implemented comprehensively and continues both in extracurricular activities and in curricular activities.Â